2007
DOI: 10.1097/sla.0b013e31813e66b9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical and Biochemical Follow-up in Medullary Thyroid Carcinoma

Abstract: The chance to achieve biochemical cure in MTC is clearly dependent on the primary tumor size. The chance for long-term biochemical cure in a pT4-tumor is almost nil even after multiple and extended reoperations, whereas a pT1 tumor can be cured in up to 67% of the patients. Long-term survival, however, can be achieved even in pT4 tumor patients in almost 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
6
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 27 publications
9
59
6
6
Order By: Relevance
“…Specific survival at 5 and 10 years in the present cohort was 79.3 and 73.6%, respectively, which was similar to previous reports (16,19,20,22,23). Another possible adverse prognostic factor identified in the present study was age >45 years.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Specific survival at 5 and 10 years in the present cohort was 79.3 and 73.6%, respectively, which was similar to previous reports (16,19,20,22,23). Another possible adverse prognostic factor identified in the present study was age >45 years.…”
Section: Discussionsupporting
confidence: 81%
“…Of the 140 patients included in the present study, only 11% represented familial cases, which indicates a prevalence significantly lower than that reported by others (6,(16)(17)(18)(19). However, the present study only included patients with MTC confirmed by histology, which may have underestimated the total number of familial cases.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In such circumstances, 10-and 20-year disease-free survival rates of our MTC series were 89 and 82.5%, respectively, and cause-specific survival rates were 96.6 and 91.7%, respectively [18]. These survival rates were better than those reported in Western countries [3,4,[10][11][12][13][14][19][20][21][22][23]. In our series, extrathyroid extension, lymph node metastasis, and a large tumor size were regarded as prognostic factors, while gender, age, and RET gene mutations (except for MEN 2B) did not affect patients' prognoses [18].…”
Section: Evaluation Of Stage Of Mtc Patientscontrasting
confidence: 44%
“…En nuestra serie a todos los pacientes con diagnóstico pre operatorio de CMT se les realizó TT asociada a disección cervical, cuya extensión se determinó según el tamaño del tumor y la presencia de linfonodos sospechosos en la ecografía preoperatoria, como se expuso en los resultados. Respeto a las características anátomo-patológicas de nuestra serie, el tamaño tumoral promedio fue de 1,8 cm, lo que es menor a lo reportado por otros grupos 3,15,27 , lo mismo ocurrió con la incidencia de compromiso linfonodal presente sólo en 20,8% de nuestros pacientes al momento del diagnóstico, el cual es reportado por distintas series entre 30-60% de los casos 3,15,27 . Dichas diferencias podrían explicarse por el diagnóstico precoz de nuestros pacientes, ya que 78,5% de ellos se presentó en etapa I y II.…”
Section: Seguimiento a Largo Plazounclassified